An Improvement on An Interest Rate Commission Agent Banking System (AIRCABS MODEL) - Tessema, Ameha Tefera; Kruger, Jan Walters (International Journal of Economics and Financial Issues, 2017)
This paper sought to test An interest rate commission agent banking model's viability and reliability. An interest rate commission agent banking system (AIRCABS) increased the investor loan funding agent bank's profitability and sustainability by shifting credit risk and liquidity crunch to investors and entrepreneurs. The bank increases stable deposit by applying discrete market deposit interest rate incentive into depositors' accounts and by letting depositors latter to shift to investor position having the bank as an agent to collect proportionate credit price instead of deposit interest rate on the portion of the fund the bank has already invested. Therefore, an interest rate commission agent bank found viable and reliable. Keywords: agent bank model, agent bank's profitability and sustainability, stable deposit JEL Classfications: E21,E22, E40, G01,G21, G32